Effect of four sessions of aerobic exercise with abdominal radiofrequency in adipose tissue in healthy women: Randomized control trial - Vale, Ana Luísa (2020)
Abdominal adiposity is a cardiovascular risk factor; it is assumed that the combination of radiofrequency and physical exercise may decrease this excess of adipose tissue. To analyze the effect of four intervention sessions on abdominal adipose tissue. The study analyzes the effect of four sessions of aerobic exercise combined with radiofrequency. Participants were 28 healthy female volunteers, aged 18-28 years, randomly assigned to an experimental group and a placebo group. They were characterized by a sociodemographic questionnaire, the International Physical Activity Questionnaire and the Food Frequency Questionnaire. The groups performed four sessions of abdominal radiofrequency followed by moderate aerobic exercise, assessing body mass, body mass index, fat mass, waist circumference, waist/height ratio, subcutaneous adipose thickness, and horizontal abdominal adipose fold at the first and fourth sessions. In the experimental group, a percentage of potency was used that allowed to maintain the temperature between 40°C and 42°C to the epidermis. In the placebo group, the power of the radiofrequency was 0 W. To compare results, Student's t test was used for a significance level of 0.05. There was a statistically significant decrease in waist circumference, abdominal subcutaneous adipose thickness, and horizontal abdominal fold in the experimental group compared to the placebo group (P < 0.05).